Studies about Snake Peptides: A Review about Brazilian Contribution - Assis, Rhayane Alves [UNESP]; Bittar, Bruno Barros; Amorim, Nathan Pereira Lima; Carrasco, Guilherme Henrique; Silveira, Elaine Divina Rodrigues; Benvindo-Souza, Marcelino; de Souza Santos, Lia Raquel (FapUNIFESP (SciELO), 2022)
The peptides present in snake venoms are studied because of their properties, constitutions, mechanisms of action and pharmacological potential. Recognizing this potential, the present study reports the contributions of Brazilian researchers about snake peptides, between 1975 and July 2020. Thus, this study serves as a basis for monitoring this theme in Brazil, referring to the trends and patterns of scientific production. The results indicated a significant increase in Brazilian scientific production over the years, highlighting institutions located in São Paulo state as, the Butantan Institute and University of São Paulo. The main journal where Brazilian authors publish their research is the Toxicon Journal. Collaborative networks were identified between Brazilian institutions and among other countries with Brazil. The most investigated species are found in brazilian territory, mainly those belonging to the genus Bothrops and the species Crotalus durissus. The increase in studies about this theme in Brazil is evident, however, a gap is highlighted for states outside the southeastern region and for other venomous species.
Keywords: Biodiversity; Bioprospecting; Brazil; Reptiles; Scientific trend